Knowledge, principles and deliberation. An interpretation of moral knowledge in Plato’s «Crito» - Solans Blasco, Miquel (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
This paper analyzes the central elements of Plato’s conception of moral knowledge in the Crito. In the first place, it studies the characterization of the moral knowledge that Socrates ascribes to himself in the Apology, with the aim of offering a framework for the attribution of moral knowledge to Socrates in the Crito. The next section is devoted to the analysis of the practical principles introduced by Socrates in his response to the offer of flight advanced by his friend Crito. These principles will guide the deliberation on whether such action should be undertaken or not, which will be treated in the fourth section. Finally, in the fifth and last section, I will focus on the dispositional aspects highlighted by the Platonic representation of Socrates and Crito and that are essential in the characterization of moral knowledge as presented in the Crito.
Keywords: Plato; moral knowledge; Crito; principles; deliberation; moral dispositions